CF2H-synthon enables asymmetric radical difluoroalkylation for synthesis of chiral difluoromethylated amines - Peng Liu; Yan He; Chen-Hui Jiang; Wei-Ran Ren; Ruo-Xing Jin; Ting Zhang; Wang-Xuan Chen; Xuan Nie; Xi-Sheng Wang (Nature Communications)
Abstract The difluoromethyl group is a crucial fluorinated moiety with distinctive biological properties, and the synthesis of chiral CF₂H-containing analogs has been recognized as a powerful strategy in drug design. To date, the most established method for accessing enantioenriched difluoromethyl compounds involves the enantioselective functionalization of nucleophilic and electrophilic CF₂H synthons. However, this approach is limited by lower reactivity and reduced enantioselectivity. Leveraging the unique fluorine effect, we design and synthesize a radical CF₂H synthon by incorporating isoindolinone into alkyl halides for asymmetric radical transformation. Here, we report an efficient strategy for the asymmetric construction of carbon stereocenters featuring a difluoromethyl group via nickel-catalyzed Negishi cross-coupling. This approach demonstrates mild reaction conditions and excellent enantioselectivity. Given that optically pure difluoromethylated amines and isoindolinones are key structural motifs in bioactive compounds, this strategy offers a practical solution for the efficient synthesis of CF₂H-containing chiral drug-like molecules.